2004
DOI: 10.3171/jns.2004.101.2.0248
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment, disability, and quality of life outcome after decompressive hemicraniectomy in malignant middle cerebral artery infarction

Abstract: Decompressive hemicraniectomy improves survival in patients with malignant MCA infarction when compared with earlier reports of conservative treatment alone. Functional outcome and QOL remain markedly impaired, especially among elderly patients and in those with a severe neurological deficit at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
124
5
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 35 publications
(42 reference statements)
12
124
5
8
Order By: Relevance
“…Out of 30 enrolled patients 14 showed signs of herniation (dilated pupil), and the time point of surgery varied broadly from 13 to 235 h after stroke [25]. Likewise, these results are supported by a prospective study of Kilincer et al identifying sings of herniation as a prognostic factor for poor outcome [31], and by several retrospective trials [32,33,34]. Furthermore, in the studies of Skoglund et al (n = 18) and Chung et al (n = 24) 67 and 100% of patients, respectively, showed signs of herniation, leading to worse neurological outcomes compared to the results of the DECIMAL and DESTINY trials [8,9,35,36].…”
Section: Surgical Treatmentsupporting
confidence: 67%
“…Out of 30 enrolled patients 14 showed signs of herniation (dilated pupil), and the time point of surgery varied broadly from 13 to 235 h after stroke [25]. Likewise, these results are supported by a prospective study of Kilincer et al identifying sings of herniation as a prognostic factor for poor outcome [31], and by several retrospective trials [32,33,34]. Furthermore, in the studies of Skoglund et al (n = 18) and Chung et al (n = 24) 67 and 100% of patients, respectively, showed signs of herniation, leading to worse neurological outcomes compared to the results of the DECIMAL and DESTINY trials [8,9,35,36].…”
Section: Surgical Treatmentsupporting
confidence: 67%
“…Age impacted outcome, with older patients having worse outcomes. 986 The authors stressed, "The decision to perform decompressive surgery should, however, be made on an individual basis in every case". [987][988][989] Although the surgery may be recommended for treatment of seriously affected patients, the physician should advise the patient's family about the potential outcomes, including survival with severe disability.…”
Section: Decompressive Surgerymentioning
confidence: 99%
“…As an alternative therapy, surgical decompression techniques (large hemicraniectomy with durotomy) have been proposed to relieve the high intracranial pressure, but this strategy remains controversial in the absence of randomized, controlled trials and the fear of severe and "unacceptable" residual disability. [3][4][5][6][7][8][9][10][11][12] This controversy in the medical literature was also apparent in the national survey that we performed in 47 French Neurology Departments in 2000, showing that only 2 centers were convinced of the efficacy of decompressive craniectomy. The majority of centers (77%) approved the concept of a randomized trial evaluating the benefit of decompressive craniectomy in patients with malignant MCA infarction (K. Vahedi, unpublished data, 2000).…”
mentioning
confidence: 99%